Freedom of Opinion from the Perspective of Islamic Law and Human Rights - Ahmad Husairi; Sarah Nur Izzati; Kurnia Saputri (Yayasan Cahaya Generasi Positif, 2026)
This research examines the right to freedom of opinion from the perspectives of Islamic law and the Declaration of Human Rights. In a democratic system, Indonesia is constitutionally required to protect freedom of expression as a non-derogable right under Article 28I paragraph (4) of the 1945 Constitution. Although essential to human dignity, this right is not absolute and may be lawfully restricted to protect public order, national security, and the rights of others. This study employs a normative juridical method by analyzing legal norms, doctrines, and theoretical frameworks governing freedom of opinion in Islamic legal thought and international human rights law. International recognition is affirmed in Article 19 of the Universal Declaration of Human Rights. The study concludes that clear, proportional, and legally grounded limitations are necessary to ensure responsible exercise within pluralistic societies. Harmonization between these frameworks can be achieved through contextual and purposive legal interpretation.